Analysis of the impact of parents' electronic screen time habits, young children's screen exposure and parent-child interaction on language development delay in young children - Wan, Xiaohong; Kang, Xiaoqing; Chen, Shunli; Du, Juan; Yan, Fang; Bai, Yongqi (Frontiers in Pediatrics, 2025)
PurposeLanguage development delay (LDD) affected 5%–10% of preschool children globally, and modifiable environmental factors such as screen exposure drew significant attention. This study aimed to evaluate how parental screen habits, children's screen exposure, and parent-child interactions collectively influenced the risk of LDD.MethodsThis study employed a retrospective case-control design involving young children who received health check-ups between October 2020 and October 2024. Participants were categorized into normal and Language Developmental Delay groups by Bayley Scales of Infant and Toddler Development-III (BSID-III). Parent and child screen time (ST) were measured using a 7-day diary. Parent-child interaction quality was assessed using the Nursing Child Assessment Teaching Scale (NCATS). Emotion regulation and parenting stress were evaluated using the Preschool Children's Emotional Regulation Strategies Questionnaire and the Parenting Stress Index.ResultsAmong 296 children (113 with LDD, 106 normal), parents in the LDD group spent significantly more time on screens daily (fathers: + 0.34 h; mothers: + 0.32 h) and had higher total entertainment time (+12.07 min). Children with LDD showed longer average daily screen exposure (+0.4 h), with 30.97% exceeding 2 h per day compared to 12.26% in the control group. The LDD group had lower parent-child interaction frequency (>3 times/week: 16.81% vs. 30.19%), lower storytelling rates (13.27% vs. 31.13%), and lower NCATS scores (96.52 vs. 99.45).ConclusionThis study emphasized the importance of modifiable environmental factors, particularly excessive parental and child ST and decreased interaction quality, in the risk of LDD. It highlighted the necessity for behavioral interventions at the family level.